(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article describes the essence and application of pedagogical innovations in the teaching of "Oscillations and Waves" in physics. In particular, the advantages of the method of teaching vibrational motion and waves on the basis of double-contrast examples, the method of teaching the department of vibrations on the basis of integrative technologies and the use of analog technologies in teaching mechanical and electromagnetic oscillations were given